2021
DOI: 10.1111/jfbc.14043
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and management of Alzheimer’s disease: Potential role of gut microbiota modulation with probiotics supplementation

Abstract: Alzheimer's disease (AD) is the leading type of dementia in aging people and is a progressive condition that causes neurodegeneration, resulting in confusion, memory loss, and deterioration of mental functions. AD happens because of abnormal twisting of the microtubule tau protein in neurons into a tangled neurofibrillary structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 199 publications
(202 reference statements)
0
7
0
Order By: Relevance
“…The development of Alzheimer's disease [69,[88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107] and the mechanisms through which the microbiome can contribute to the progression of Alzheimer's disease have been investigated . Numerous studies are also available regarding treatments with probiotics [139][140][141][142]. In one study [143], it was observed that the consumption of a combined probiotic preparation (Lactobacillus acidophilus, Lactobacillus casei, Bifidobacterium bifidum, and Lactobacillus fermentum) for 12 weeks had a significantly positive impact on the cognitive abilities of the study participants in the Mini-Mental State Examination compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The development of Alzheimer's disease [69,[88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107] and the mechanisms through which the microbiome can contribute to the progression of Alzheimer's disease have been investigated . Numerous studies are also available regarding treatments with probiotics [139][140][141][142]. In one study [143], it was observed that the consumption of a combined probiotic preparation (Lactobacillus acidophilus, Lactobacillus casei, Bifidobacterium bifidum, and Lactobacillus fermentum) for 12 weeks had a significantly positive impact on the cognitive abilities of the study participants in the Mini-Mental State Examination compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a systematic review and meta-analysis by Hung et al [ 68 ] observed a significant reduction in the diversity of the gut microbiome of individuals with AD compared to healthy controls. Furthermore, pathogenic microorganisms may contribute to the pathophysiology of AD through the generation of lipopolysaccharides and bacterial amyloid fiber [ 69 , 70 ]. The beneficial effects of probiotics can depend on their strain, but research has linked some species of probiotic bacteria to antioxidant defense [ 71 ].…”
Section: Probioticsmentioning
confidence: 99%
“…Gastrointestinal dysfunction is highly prevalent in PD and can precede motor symptoms by more than a decade [79]. Thus, it may be directly related to the process of α-synuclein misfolding, since it is already well documented that PD patients have α-synuclein aggregates in their colon [77,80,[83][84][85].…”
Section: Gut Microbiota and Pdmentioning
confidence: 99%